Associations Between Albumin/Neutrophil-to-Lymphocyte Ratio Score and New-Onset Atrial Fibrillation in Patients with Acute Myocardial Infarction Undergoing PCI - Yang SB; Zhao HW (Journal of Inflammation Research)
Shao-Bing Yang,1 Hong-Wei Zhao2 1Department of Cardiology, The General Hospital of Ningxia Medical University, Yinchuan, People’s Republic of China; 2Department of Cardiology, The Seventh Affiliated Hospital of Sun Yat-Sen University, Shenzhen, People’s Republic of ChinaCorrespondence: Hong-Wei Zhao, Email zhaohongwei@sysush.comBackground: Inflammation was associated with the increased risk of atrial fibrillation (AF). As a novel inflammatory indicator, albumin/neutrophil-to-lymphocyte ratio score (ANS) has been demonstrated to associate with coronary artery disease. However, the relationship between ANS and new onset atrial fibrillation (NOAF) in patients with acute myocardial infarction (AMI) underwent PCI was not determined.Methods: A total of 2410 AMI patients underwent PCI were consecutively included between March 2020 and December 2023. Patients were divided into NOAF group and control group according to the occurrence of NOAF during hospitalization. The ANS was calculated and analyzed, so as to determine its predictive value in the presence of NOAF in AMI patients after PCI.Results: In total, 88 (3.7%) individuals developed NOAF during hospitalization. We found that NOAF was associated with older age, greater LA, higher NT-proBNP, ANS and Killip ≥ 2. The ANS exhibited an accurately predictive value for the NOAF (area under the curve [AUC], 0.695; 95% CI, 0.649– 0.740, P < 0.001). Moreover, when divided into three groups according to the tertile of ANS, patients in tertile 1 (lowest in ANS) showed a 2.214-fold increased risk of NOAF in comparison to those in the tertile 3 (HR, 2.214; 95% CI 1.804– 5.101; P = 0.029).Conclusion: ANS is a robust tool for the prediction of NOAF in AMI patients underwent PCI. Therefore ANS could be used for risk prediction and optimal management for NOAF in AMI patients after PCI.Keywords: albumin/neutrophil-to-lymphocyte ratio score, new-onset atrial fibrillation, acute myocardial infarction, PCI